2010
DOI: 10.1242/jeb.037242
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of genetically determined growth variation in bivalve larvae (Crassostrea gigas)

Abstract: Bayne, 2004b). For bivalve larvae, Pace and colleagues have shown that a complex set of physiological processes regulate differences in genetically determined growth rates, including differential feeding rates and protein metabolism. These comparisons between fast-and slowgrowing families of larvae provide clear experimental advantages for understanding the mechanisms of growth heterosis during development. Accepted 27 November 2009 SUMMARY Growth rates in animals are governed by a wide range of biological fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 76 publications
2
48
0
Order By: Relevance
“…Genes exhibiting expression patterns unique to particular taxa or phenotypes are more likely to have evolved to enable novel life histories (Whitehead, 2012;Whitehead et al, 2011). The comparative approach can be further improved by integrating phylogeny (Whitehead, 2012) or genetic background (Meyer and Manahan, 2010) into downstream analyses. For example, if three or more species or populations are being compared and a robust phylogeny is available, one may test whether the transcriptomic response across species is consistent with neutral expectations or rejects neutral expectations.…”
Section: Improving Experimental Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes exhibiting expression patterns unique to particular taxa or phenotypes are more likely to have evolved to enable novel life histories (Whitehead, 2012;Whitehead et al, 2011). The comparative approach can be further improved by integrating phylogeny (Whitehead, 2012) or genetic background (Meyer and Manahan, 2010) into downstream analyses. For example, if three or more species or populations are being compared and a robust phylogeny is available, one may test whether the transcriptomic response across species is consistent with neutral expectations or rejects neutral expectations.…”
Section: Improving Experimental Designsmentioning
confidence: 99%
“…Within the field of environmental physiology, transcriptomics has been used successfully to address a broad range of questions concerning how or whether organisms can acclimate or adapt to the abiotic conditions associated with life in specific habitats (Evans and Hofmann, 2012). These investigations have demonstrated the complexity of responses to the environment (Chapman et al, 2011;Evans et al, 2011), isolated cellular and physiological processes that are robust or sensitive to environmental change (Logan and Somero, 2010), provided clues as to how organisms cope with life in challenging habitats (Podrabsky and Somero, 2004;Bilyk and Cheng, 2013), helped to predict vulnerabilities or resistance toward climate change (Barshis et al, 2013;Palumbi et al, 2014) and highlighted potentially important genes for future study (Meyer and Manahan, 2010;Whitehead et al, 2013), as well as leading to many other valuable scientific discoveries. However, like any other experimental approach, transcriptomics is associated with a set of limitations, and some have questioned the adequacy of transcriptomics to address particular questions of interest to environmental physiologists (Feder and Walser, 2005;Suarez and Moyes, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Constitutive (i.e., genetic) differences between fast and slow growing bivalves have long been related to variable degrees of multi-locus heterozygosity (Bayne and Hawkins, 1997;Garton et al, 1984;Hawkins, 1995;Hawkins et al, 1986;Holey and Foltz, 1987;Meyer and Manahan, 2010;Pace et al, 2006;Toro and Vergara, 1998). It seems to be well established that increasing heterozygosity causes the reduction of the metabolic costs associated to protein deposition (Bayne and Hawkins, 1997;Hawkins et al, 1986Hawkins et al, , 1989 this being a physiological factor contributing to the maximization of energy budget in fast growing individuals.…”
Section: Acute and Acclimated Physiological Responses Of F And S Clammentioning
confidence: 99%
“…Peterson et al studied the differential mRNA expression of IGF-I and IGF-II in slow and fast-growth catfish [14]. Studies examining the differential gene expression in a FG phenotype in Pacific oyster Crassostrea gigas [15, 16] identified genes overrepresented in screens of growth heterosis, 50% of which were ribosomal proteins, indicating the importance of translational regulation in fast growth [17]. Several of these studies were on single growth factors, but Pace et al [18] showed that a range of environmental and metabolic variables can affect growth heterosis and that these interactions are very complex.…”
Section: Introductionmentioning
confidence: 99%